Improvement of the Quality Group of Critical Railway Castings from 110G13L Steel - Chaikin, Andrey V.; Chaikin, Vladimir A.; Bykov, Petr O.; Kuandykov, Almaz B. (Engineering, Technology & Applied Science Research, 2025)
This paper presents the results of industrial tests to improve the technological process of smelting 110G13L steel to increase mechanical properties, improve the quality group and operational reliability of critical railway castings, and reduce the cost of steel. Using statistical and regression analyses, the advantages of a comprehensive approach were revealed on metal when using innovative diffusion deoxidizers in the following areas: organizing early slag induction during charge melting, increasing the efficiency of diffusion deoxidation of steel due to the use of a Diffusion Aluminum-containing Deoxidizer (DAD), and extra furnace treatment of the melt in a ladle with a Universal Refining Mixture (URM), providing an adsorption-flotation method of steel refining. The main advantage of the diffusion deoxidizers developed is that they have a high dispersion that significantly increases their reactivity. The implementation of the proposed directions to improve the technological process of smelting 110G13L steel for critical railway castings in combination with the optimization of the chemical composition of steel and slag allowed a significant increase in the number of first-quality group smelts from 29% to 71% while reducing cost.